2014
DOI: 10.1136/annrheumdis-2014-eular.2837
|View full text |Cite
|
Sign up to set email alerts
|

OP0297 Calprotectin (S100A8/9) as Serum Biomarker for Clinical Response in Proof-Of-Concept Trials in Axial and Peripheral Spondyloarthritis

Abstract: Background Biomarkers complementing clinical evaluations may help to reduce the length and size of proof-of-concept (PoC) trials aimed to obtain quick “go/no go” decisions in the clinical development of new treatments. Objectives We aimed to identify and validate serum biomarkers to predict clinical response in spondyloarthritis (SpA) PoC trials. Methods The candidate biomarkers high sensitive-C-reactive protein (hs-CRP), interleukin-6 (IL-6), pentraxin-3 (PTX-3), alpha-2-macroglobulin (alpha-2-MG), matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Studies have shown that TNF inhibitors improve healthrelated quality of life, patient-reported outcomes, anemia, Creactive protein (CRP) levels, and sleep quality in patients with AS because TNF inhibitors control inflammation in the spine, as measured by various MRI sequences [14] . In the current study we found that mean serum level of hs-CRP higher in patients treated with conventional treatment, than in patients on biological treatment (infliximab infusion) and this difference is statistically significant (P-value = 0.0235) and these results were in accordance with other study done by Turina et al who found that hs-CRP is a useful biomarker of inflammation in this context as, despite not being elevated in all patients at baseline, it rapidly and significantly decrease in both axial and peripheral SpA treated with either infliximab or etanercept [15] . In the current study we found that mean level of ESR higher in patients treated with conventional treatment, than in patients on biological treatment (infliximab infusion) and this difference is not statistically significant (P-value = 0.3051) which disagrees with Luc et al that is found that there was a strong association between ESR level at baseline and clinical response to treatment with anti-TNF after 3 months, supporting a potential distinctive exploitation of ESR in identifying AS patients suitable for treatment with anti-TNF, which is also of particular relevance in light of the costs of biologics and the side effects of these drugs and this disagreement due to difference in sample size and difference in study population [16] .…”
Section: Discussionsupporting
confidence: 91%
“…Studies have shown that TNF inhibitors improve healthrelated quality of life, patient-reported outcomes, anemia, Creactive protein (CRP) levels, and sleep quality in patients with AS because TNF inhibitors control inflammation in the spine, as measured by various MRI sequences [14] . In the current study we found that mean serum level of hs-CRP higher in patients treated with conventional treatment, than in patients on biological treatment (infliximab infusion) and this difference is statistically significant (P-value = 0.0235) and these results were in accordance with other study done by Turina et al who found that hs-CRP is a useful biomarker of inflammation in this context as, despite not being elevated in all patients at baseline, it rapidly and significantly decrease in both axial and peripheral SpA treated with either infliximab or etanercept [15] . In the current study we found that mean level of ESR higher in patients treated with conventional treatment, than in patients on biological treatment (infliximab infusion) and this difference is not statistically significant (P-value = 0.3051) which disagrees with Luc et al that is found that there was a strong association between ESR level at baseline and clinical response to treatment with anti-TNF after 3 months, supporting a potential distinctive exploitation of ESR in identifying AS patients suitable for treatment with anti-TNF, which is also of particular relevance in light of the costs of biologics and the side effects of these drugs and this disagreement due to difference in sample size and difference in study population [16] .…”
Section: Discussionsupporting
confidence: 91%